Prinsip-Prinsip Pembelajaran di Sekolah Dasar, Pengetahuan Alam dan Ilmu Pengetahuan Alam - Rara Dini Alianti; Namira Alfia Hikma; Dita Sabilla Azahra; Adzra Kamila Paustina; Vira Febrianty; Zahra Marta Hafidzah; Nurul Aulia Rahma; Wati Sukmawati (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This article discusses the importance of Knowledge and Natural Science in elementary schools as a foundation for developing students' character and skills. This study uses a descriptive qualitative method to explore teachers' experiences in teaching science, the challenges faced, and the strategies implemented to improve students' understanding. The results of the study indicate that an approach involving real-world experiences and technology can strengthen the understanding of scientific concepts. In addition, this article provides recommendations for teacher professional development to improve the quality of science education in elementary schools.